Contribution of ribosomal residues to P-site tRNA binding - Shoji, Shinichiro (Oxford University Press, 2009)
Structural studies have revealed multiple contacts between the ribosomal P site and tRNA, but how these contacts contribute to P-tRNA binding remains unclear. In this study, the effects of ribosomal mutations on the dissociation rate (k(off)) of various tRNAs from the P site were measured. Mutation of the 30S P site destabilized tRNAs to various degrees, depending on the mutation and the species of tRNA. These data support the idea that ribosome-tRNA interactions are idiosyncratically tuned to ensure stable binding of all tRNA species. Unlike deacylated elongator tRNAs, N-acetyl-aminoacyl-tRNAs and tRNA(fMet) dissociated from the P site at a similar low rate, even in the presence of various P-site mutations. These data provide evidence for a stability threshold for P-tRNA binding and suggest that ribosome-tRNA(fMet) interactions are uniquely tuned for tight binding. The effects of 16S rRNA mutation G1338U were suppressed by 50S E-site mutation C2394A, suggesting that G1338 is particularly important for stabilizing tRNA in the P/E site. Finally, mutation C2394A or the presence of an N-acetyl-aminoacyl group slowed the association rate (k(on)) of tRNA dramatically, suggesting that deacylated tRNA binds the P site of the ribosome via the E site.